Heat transfer enhancement in confined slot jets using water-based Cu core-shell and double-shell nanofluids under forced convection conditions - Benmouhoub, Dahbia; Iachachene, Farida; Dalkilic, Ahmet Selim (ELSEVIER SCIENCE INC, 2026)
Heat transfer from confined slot jets is important in several thermal engineering applications, including electronics cooling and turbine blade temperature control. This study presents a numerical investigation of a confined slot jet impinging on a heated wall under forced convection using core-shell nanofluids. The objective is to evaluate the influence of nanoparticle architecture on heat transfer performance. Several configurations are considered, including Cu@Ag, Cu@Au, Cu@Au@Ag, and Cu@Ag@Au. The flow and heat transfer are modeled by solving the Reynolds-Averaged Navier-Stokes equations with the Reynolds Stress Model (RSM) and enhanced wall treatment for Reynolds numbers between 10,000 and 25,000 and nanoparticle volume fractions up to 5%. The numerical approach is validated against data available in the literature. The performance of various core-shell nanofluids was evaluated in terms of heat transfer enhancement efficiency relative to the conventional Cu-water nanofluid. Among them, Cu@Au nanofluids demonstrated the highest improvement, ranging from 32.87% to 43.06%, ranking first. The results also indicate that heat transfer enhancement shows only a weak dependence on Reynolds numbers. These findings suggest that significant heat transfer enhancement is possible with low nanoparticle concentrations, providing practical advantages by minimizing stability and agglomeration issues.
Keywords: Heat Transfer; Turbulent Jet Impingement; CFD; Nanofluid; Core-Shell Nanoparticles; HYBRID NANOFLUID; THERMAL-CONDUCTIVITY; FLOW; Thermodynamics; Engineering; Mechanics